Identification and analysis of the antigens detected by two commercial Bacillus cereus diarrheal enterotoxin immunoassay kits. - Beecher, D J (1994)
The usefulness of two commercial immunoassays for the detection of diarrheal enterotoxin of Bacillus cereus is unclear because the identity of the enterotoxin(s) has not been proven and the kits detect different proteins. We found that the Bacillus cereus Enterotoxin-Reversed Passive Latex Agglutination kit (Oxoid) detects the L2 component from hemolysin BL, and the Bacillus Diarrhoeal Enterotoxin Visual Immunoassay (Tecra) detects two apparently nontoxic proteins.